2011
DOI: 10.1186/1471-2458-11-s3-s2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of screening and management of diabetes during pregnancy on stillbirths

Abstract: BackgroundDiabetes during pregnancy is associated with significant risk of complications to the mother, fetus and newborn. We reviewed the potential impact of early detection and control of diabetes mellitus during pregnancy on stillbirths for possible inclusion in the Lives Saved Tool (LiST).MethodsA systematic literature search up to July 2010 was done to identify all published randomized controlled trials and observational studies. A standardized data abstraction sheet was employed and data were abstracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 82 publications
0
35
0
8
Order By: Relevance
“…Syed et al [170] showed that there was a non-significant reduction in the risk of stillbirths (RR 0.20; 95% CI: 0.03 to 1.10) when intensive management protocols were utilized as opposed to conventional management. Optimum control versus sub-optimum control of diabetes significantly reduced perinatal mortality (RR 0.4; 95% CI: 0.25 to 0.63) [170].…”
Section: Management Of Diabetesmentioning
confidence: 99%
“…Syed et al [170] showed that there was a non-significant reduction in the risk of stillbirths (RR 0.20; 95% CI: 0.03 to 1.10) when intensive management protocols were utilized as opposed to conventional management. Optimum control versus sub-optimum control of diabetes significantly reduced perinatal mortality (RR 0.4; 95% CI: 0.25 to 0.63) [170].…”
Section: Management Of Diabetesmentioning
confidence: 99%
“…The consequences of hypoglycemia and perinatal depression may present within the first 24 hours of life, whereas the con sequ ences of hypocalcemia and hypomagnesemia most frequently manifest between 24 and 72 hours after birth (23). The incidence of congenital malformations has been 3-5 times increased in the infants of diabetic mothers (24,25). In our sample, 16.22% of newborn infants presented with a heart defect.…”
Section: Discussionmentioning
confidence: 62%
“…Identifying the gestational diabetics' early and intensive management and regular multidisciplinary follow up is the reason for the improved outcome in this patients. 24 Placental causes have been recognized as an important contributor for stillbirths. It is difficult to label placental cause without clinical evidence of placental insufficiency or obvious placental abnormalities.…”
Section: Discussionmentioning
confidence: 99%